2009
DOI: 10.1108/02683940910996806
|View full text |Cite
|
Sign up to set email alerts
|

Emotional labor: links to work attitudes and emotional exhaustion

Abstract: Purpose -The purpose of this study is to explore the links from self-focused emotional labor (surface acting) and other-focused emotional labor (emotional enhancement) to job satisfaction, affective commitment, emotional exhaustion, and intentions to quit. Design/methodology/approach -The study employed a cross-sectional survey of 363 nurses' aides and childcare workers. Findings -Surface acting, a type of self-focused emotional labor, was related to negative work outcomes (lower job satisfaction and affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 44 publications
7
68
0
2
Order By: Relevance
“…In accordance with the results of international research (Gardney, 2003;Hwa, 2012;Judge et al, 2009;Morris, & Feldman, 1996;Seery & Corrigall, 2009;Totterdell, & Holman, 2003), analyses have demonstrated that surface role-playing is correlated with a higher level of professional burnout, whereas there is no such correlation in the case of deep acting.…”
Section: Discussion Of the Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…In accordance with the results of international research (Gardney, 2003;Hwa, 2012;Judge et al, 2009;Morris, & Feldman, 1996;Seery & Corrigall, 2009;Totterdell, & Holman, 2003), analyses have demonstrated that surface role-playing is correlated with a higher level of professional burnout, whereas there is no such correlation in the case of deep acting.…”
Section: Discussion Of the Resultssupporting
confidence: 73%
“…As Brotheridge and Gardney (2002) conclude: although both surface and deep acting allow employees to express the emotions desired by the organisation, the physiological state produced by the actual emotions felt remains, which may negatively influence employee health and level of stress. The effect of such influence may be the emergence of professional burnout in an employee affected by emotional labour (Babakus et al, 2011;Brotheridge & Grandey, 2002;Grandey, 2003;Hochschild, 2009;Hülsheger & Schewe, 2011, Hwa, 2012Jin & Guy, 2009, Maslach, Schaufeli & Leiter, 2001Seery & Corrigall, 2009, Zapf, Seifert, Schmutte, & Mertini, & Holz, 2001). …”
Section: Emotional Labourmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research has investigated the impact of the work environment on these key dimensions of burnout (Seery and Corrigall 2009;Canivet et al 2010), but as of yet there has been limited work on examining the mechanisms by which both dimensions influence key work attitudes. In line with previous studies (Thanacoody, Bartram and Casimir 2009;Cole, Bernerth, Walter and Holt 2010), we treat emotional exhaustion as the main explanatory variable to understand the lack of commitment and high levels of turnover intentions among health-care professionals, but use the COR to explain how disengagement might mediate its impact rather than act separately as a antecedent.…”
Section: Emotional Exhaustionmentioning
confidence: 99%
“…Research has indicated that surface acting may lead to reduced employee health and well-being, lower job satisfaction and organizational commitment, and increased turnover intentions (Brotheridge & Lee, 2003;Grandey, 2003;Johnson & Spector, 2007 Woolf, & Hurst, 2009;Seery & Corrigall, 2009). On the other hand, frequent use of deep acting has been observed to have positive consequences for the employees as well as for the organization.…”
Section: Introductionmentioning
confidence: 98%